Decreased ventricular size and mass mediate the reduced exercise capacity in adolescents and adults born premature. (September 2021) - McKay, Lauren; Goss, Kara N.; Haraldsdottir, Kristin; Beshish, Arij G.; Barton, Gregory P.; Palta, Mari; Chesler, Naomi C.; François, Christopher J.; Wieben, Oliver; Macdonald, Jacob A.; Eldridge, Marlowe W.; Watson, Andrew M.
Abstract: Background: Premature birth is associated with lower levels of cardiorespiratory fitness (CRF) but the underlying mechanisms responsible remain unclear. This study assessed whether differences in cardiac morphology or function mediate differences in CRF among adolescents and young adults born preterm. Methods: Adolescents and young adults born moderately to extremely premature (gestational age ≤ 32 weeks or birth weight < 1500 g) and age-matched term born participants underwent resting cardiac MRI and maximal exercise testing. Mediation analysis assessed whether individual cardiovascular variables accounted for a significant proportion of the difference in maximal aerobic capacity between groups. Results: Individuals born preterm had lower VO2max than those born term (41.7 ± 8.6 v 47.5 ± 8.7, p  < 0.01). Several variables differed between term and preterm born subjects, including systolic and diastolic blood pressure, mean pulmonary artery pressure, indexed left ventricular end-diastolic volume (LVEDVi), right ventricular end-diastolic volume (RVEDVi), LV mass (LVMi), LV stroke volume index (LVSVi), and LV strain ( p  < 0.05 for all). Of these variables, LVEDVi, RVEDVi, LVSVi, LVMi, and LV longitudinal strain were significantly related to VO2max (p < 0.05 for all). Significant portions of the difference in VO2max between term and preterm born subjects were mediated by LVEDVi (74.3%, p  = 0.010), RVEDVi (50.6%, p  = 0.016), and LVMi (43.0%, p  = 0.036). Conclusions: Lower levels of CRF in adolescents and young adults born preterm are mediated by differences in LVEDVi, RVEDVi, and LVMi. This may represent greater risk for long-term cardiac morbidity and mortality in preterm born individuals. Highlights: Individuals born preterm have lower VO2max . Little is known in terms of mechanistic insight. Lower fitness in preterm individuals is mediated by cardiac differences.